Pillararene-based assemblies : design principle, preparation and applications - Zhang, Huacheng (2014)
In this review, we highlight recent advancements on pillararene-based assemblies. The driving forces for the formation of the pillararene-based assemblies are discussed first. The host–guest interactions are deemed as not only general strategy for constructing assemblies but also essential components for preventing the assemblies from the dissociation. Solvent effect is also important in the assembling process, since it could influence the host–guest interactions and provide solvophobic effect on pillararenes for the assembly. Then, several pillararene-based assembly architectures are introduced, including pillararene-based interlocked structures, such as (poly)pseudorotaxanes, (poly)rotaxanes, and daisy chains, classified by their topological structures and synthetic strategy. The morphologies of the supramolecular assemblies are divided into several types, for example, nanospheres, nanotubes and supramolecular polymers. Furthermore, the functions and potential applications are summarized accompanied with related assembly structures. The review not only provides fundamental findings, but also foresights future research directions in the research area of pillararene-based assemblies.